A Review of Barriers That Hinder Households To Separate Solid Waste at Source - Arshad, Nur Azqiah Mohammad; Zainudin, Ainur Zaireen; Adawiyah, Siti Radiaton; Ridzuan, Muhd; Norhidayah, Md Yunus (School of Social Sciences, USM, 2017)
Starting from 1 September 2015, the government of Malaysia has launched a waste separation program where households in Putrajaya, Kuala Lumpur, Melaka, Negeri Sembilan, Johor, Pahang, Perlis and Kedah have to separate their solid waste according to its composition. However, after one year of implementation, the participation of households in this program is still low. Thus, this paper reviews the barriers of solid waste separation at source based on the results gained from previous researches that have been conducted around the world. It was identified from the review that the barriers could be divided into five (5) main categories namely facility, attitude, knowledge, commitment and enforcement. These barriers could be among the issues that hindering total participation of Malaysian society in the country’s solid waste separation program. Further research should be conducted to identify which of these barriers that has contributed most to the poor participation of Malaysian society in the program. Clear understanding on the actual problem in executing the program may then lead to the formulation of the right and effective strategy and policy for solid waste separation at source initiatives in Malaysia.